Survival rate of dental implant placement by conventional or flapless surgery in controlled type 2 diabetes mellitus patients: A systematic review - Kalpana Singh; Jitendra Rao; Tuba Afsheen; Bhawna Tiwari (Wolters Kluwer Medknow Publications, 2019)
Introduction: Dental implant may serve as a choice of treatment for replacement of missing tooth in diabetic patients with their well-controlled glycemic index. To minimize postoperative complications, dental surgical procedures comprises mainly two types, namely conventional and flapless surgery. Objective: The aim of this review is to find the survival rate of the dental implant when placed with either of the technique, that is, conventional or flapless in patients with controlled Type 2 diabetes mellitus from published studies. Materials and Methods: A total of 14 studies were included from PubMed database related to the survival rate of dental implant placement by conventional or flapless surgery among patients with controlled diabetes mellitus. The cumulative mean of dental implant survival rate by conventional and flapless techniques calculated from included studies is 94.2% and 92.3%, respectively. Conclusion: The survival rate of dental implant placement by conventional and flapless techniques is similar. As few studies on flapless technique are available, therefore researchers in future should explore its advantages and disadvantages.